2006
DOI: 10.1002/dvdy.20964
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophin‐3 ameliorates sensory–motor deficits in Er81‐deficient mice

Abstract: Two factors, the ETS transcription factor ER81 and skeletal muscle-derived neurotrophin-3 (NT3), are essential for the formation of muscle spindles and the function of spindle afferent-motoneuron synapses in the spinal cord. Spindles either degenerate completely or are abnormal, and spindle afferents fail to project to spinal motoneurons in Er81 null mice; however, the interactions between ER81 and NT3 during the processes of afferent neuron and muscle spindle development are poorly understood. To examine if o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 76 publications
4
7
1
Order By: Relevance
“…A possible explanation was that an increase in the number of Ia sensory neurons was directly responsible for the larger Ia inputs to MNs. Embryonic overexpression of NT3 is known to result in increased numbers of muscle spindles and Ia afferents (Oakley et al, 1995;Wright et al, 1997;Li et al, 2006), including a moderate increase in the number of large-diameter sensory afferents in mlc/NT3 mice (Taylor et al, 2001). We found no significant increase in the density of Ia collateral axons in the ventral horns of mlc/NT3 mice, however.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…A possible explanation was that an increase in the number of Ia sensory neurons was directly responsible for the larger Ia inputs to MNs. Embryonic overexpression of NT3 is known to result in increased numbers of muscle spindles and Ia afferents (Oakley et al, 1995;Wright et al, 1997;Li et al, 2006), including a moderate increase in the number of large-diameter sensory afferents in mlc/NT3 mice (Taylor et al, 2001). We found no significant increase in the density of Ia collateral axons in the ventral horns of mlc/NT3 mice, however.…”
Section: Discussioncontrasting
confidence: 55%
“…In examining the influence of NT3 on the formation of sensory motor synapses in mice lacking the transcription factor Er81 (Li et al, 2006), we discovered an additional unexpected role of this neurotrophin in the development of the stretch reflex circuit. Prenatal exposure to elevated levels of NT3 results in a major disruption of the pattern of monosynaptic connections between Ia afferents and MNs.…”
Section: Introductionmentioning
confidence: 99%
“…In DRG explants cultured from E11.5 and E12.5 embryos, NT3 but not NGF rapidly (within 3 h) induces the expression of Er81 immunoreactivity suggesting the direct regulation of this transcription factor by NT3 . Since ventral spinal cord projection and monosynaptic inputs from Ia afferents to motoneurons are restored in Er81 mutant mice transgenically expressing NT3 under the control of the myogenin promoter (Li et al 2006), NT3 appears to act independently of Er81 on central proprioceptor targeting.…”
Section: Ngf Affects Expression Of Ttxr Sodium Conductances In Drg Nementioning
confidence: 99%
“…In the absence of ER81, most Ia afferents fail to project into the ventral horn and do not form monosynaptic connections with homonymous motor neurons (Arber et al, 2000;Kucera et al, 2002). Of interest, the few remaining Ia-motor neuron connections are correct, indicating that ER81 is not responsible for the exquisite specificity of these monosynaptic connections (Li et al, 2006). PEA3 function in motor neurons is better understood.…”
Section: Introductionmentioning
confidence: 99%
“…Other earlier factors must establish the competence to express PEA3, because only the appropriate motor neurons express PEA3 upon exposure to GDNF in vitro (Haase et al, 2002). Neurotrophin-3 (NT3) triggers expression of ER81 in sensory neurons, but not in motor neurons (Patel et al, 2003;Li et al, 2006). We have previously shown that peripheral signals sculpt Er81 expression in motor neurons from a broader competence domain (Wang and Scott, 2004).…”
Section: Introductionmentioning
confidence: 99%